A General Contingency Theory of Management - Luthans, Fred; Stewart, Todd I. (Academy of Management Review, 1977)
Recent formal recognition of situational influences on the management of complex organizations has led to an increasing number of contingency models, but a comprehensive and integrative theoretical framework for contingency management has been lacking. A General Contingency Theory (GCT) of Management is introduced as an overall framework that integrates the diverse process, quantitative and behavioral approaches to management; incorporates the environment; and begins to bridge the gap between management theory and practice